Lentiviral Vector Platform for Production of Bioengineered Recombinant Coagulation Factor VIII - Spencer, H Trent (Nature Publishing Group, 2011)
Patients with hemophilia A present with spontaneous and sometimes life-threatening bleeding episodes that are treated using blood coagulation factor VIII (fVIII) replacement products. Although effective, these products have limited availability worldwide due to supply limitations and product costs, which stem largely from manufacturing complexity. Current mammalian cell culture manufacturing systems yield around 100 µg/l of recombinant fVIII, with a per cell production rate of 0.05 pg/cell/day, representing 10,000-fold lesser production than is achieved for other similar-sized recombinant proteins (e.g. monoclonal antibodies). Expression of human fVIII is rate limited by inefficient transport through the cellular secretory pathway. Recently, we discovered that the orthologous porcine fVIII possesses two distinct sequence elements that enhance secretory transport efficiency. Herein, we describe the development of a bioengineered fVIII product using a novel lentiviral-driven recombinant protein manufacturing platform. The combined implementation of these technologies yielded production cell lines that biosynthesize in excess of 2.5 mg/l of recombinant fVIII at the rate of 9 pg/cell/day, which is the highest level of recombinant fVIII production reported to date, thereby validating the utility of both technologies.